Fertility-Related Concerns and Marital Adjustment in Women with Reproductive Health Problems (Journal of Social Sciences Review, 2025)
This study emphasized the role of concerns related to fertility in women facing reproductive health issues and its relative impact on their marital adjustment. The study hypothesized that these fertility related concerns (social concern, sexual concern, relationship concern, need for parenthood, rejection of childfree lifestyle) would have a relationship with marital adjustment. Sample of 80 married women (M= 29.4 & SD= 3.75) was selected through purposive sampling from gynae outdoors and wards of both government and private hospitals. Assessment tools include Fertility Problem Inventory (FPI; Glavac, Newton & Sherrad, 1999) and Dyadic Adjustment Scale (DAS; Spanier, 1979). Results showed that adjustment in women with reproductive health problems social concern, sexual concern, relationship concern, need for parenthood, rejection of childfree lifestyle had a negative correlation and a prediction relationship with marital adjustment. It suggests the need for supportive therapy for couples in order to overcome the distress associated with these reproductive health problems on marital adjustment.
Keywords: Fertility Related Concerns; Infertility; Marital Adjustment